Genetic Insights and Trait Relationships in Domesticated Snakeskin Gourami (Trichopodus pectoralis): A Focus on Growth and Related Traits at Harvest (Early view) - Onprang Sutthakiet, Thanathip Suwanasopee, Uthairat Na-Nakorn and Skorn Koonawootrittriron, (Tropical Life Sciences Research, 2026)
Phenotypic variation in aquaculture species is shaped by genetic and environmental factors, influencing adaptability, growth performance, and commercial value. For the snakeskin gourami (Trichopodus pectoralis), a high-value species widely cultivated in Southeast Asia, integrated knowledge of the phenotypic and genetic relationships among key growth traits remains limited. This study aimed to quantify phenotypic variation, sexual dimorphism, and genetic parameters and to assess interrelationships among harvest traits to support selective breeding strategies. A total of 8,345 fish harvested at 9 months were measured for body weight (BW), total length (TL), corrected length (CL), body thickness (BT), body depth (BD), and Fulton’s condition factor (K). Phenotypic analyses and a multi-trait animal model were applied to estimate variance components, heritability, common environmental effects (c²), and phenotypic and genetic correlations. Females exhibited significantly larger size and greater trait variation than males, while most fish fell within the smaller commercial categories (XXS, XS, S). Heritability estimates were low (0.059–0.190), and c² values ranged from low to moderate (0.063–0.214). Strong phenotypic and genetic correlations were detected among growth traits, except for a weak genetic association between TL and K. Overall, the pronounced sexual dimorphism, low heritability, and high trait interdependencies highlight the importance of multi-trait and sex-informed selection approaches to enhance growth efficiency and improve commercial outcomes in snakeskin gourami aquaculture.